INNV-43. MORE THAN WHAT MEETS THE EYE: ETMR AN UNDER RECOGNISED ATYPICAL BRAINSTEM PRIMARY. A RARE BRAIN TUMOR CONSORTIUM (RBTC) STUDY. (12th November 2021) - Khan, Sara; Solano-Paez, Palma; Hansford, Jordan R; Lu, Mei; Al-karmi, Salma; Leung, Lydia; Plant-Fox, Ashley; Spina, Melina La; Andrew, Eden; Dunham, Christopher; Phillips, Joanna; Ridola, Rita; et al.
Abstract: 10% of all pediatric brain tumors arise in the brainstem. Amongst these gliomas are the most common while other entities are rare and infrequently described in the literature. In this study we investigated the prevalence of non-gliomatous tumors in the brainstem. Amongst the 1323 embryonal tumours received at the RBTC, we identified 17 cases of ETMRs (17/165) that presented as brainstem primaries. Previously grouped within CNS-PNETs, ETMR, is a new WHO diagnostic entity, characterized by C19MC alterations. ETMR is a disease of infancy, the clinical spectrum of which is poorly understood. ETMRs arise at multiple CNS locations including cerebrum being most common (60%, ) followed by cerebellum (18%) and midline structures (6%); notably 10% were brainstem primaries, mimicking DIPG radiologically. All patients presented with a short history of progressive neurological symptoms, with most common signs and symptoms of cranial neuropathies, long tract signs and gait disturbance. Median age at diagnosis was 27 months (range 16-75months) with a male to female ratio of 0.9:1. Predominantly localized (M0-94%, M2-3 -6%) majority of patients underwent upfront biopsy or partial resection (15/17:88%), while complete tumor resection was achieved in 2 cases. All patients received heterogenous combination of chemotherapy with and without radiotherapy. Majority of patients progressed rapidly with median time to progression of 4 months and overall survival of < 13 months. The only long-term surviving patient had complete resection dose intensified chemotherapy and radiation (OS 202months). Primary ETMRs in the brainstem are under recognised entities and carry a dismal prognosis. Although rapidly progressive, prompt recognition, maximal resection and management with multimodal adjuvant therapy should be considered in cases with brainstem disease.